The correlation of exclusive breastfeeding toward decreasing of infectious diseases in baby aged 6-12 months - Fadhilah, Diinah; Widyastuti, Yani; Arum, Dyah Noviawati Setya (Jurnal Kesehatan Ibu dan Anak, 2018)
Infant mortality Rate in Indonesia has increased in the last 5 years. The cause of death in infants aged 29 days to 11 months is dominated by infectious diseases. Previous research suggests that infectious diseases can be prevented by breastfeeding. Whereas Exclusive Breastfeeding coverage in Sleman District has increased over the last 5 years. The purpose of this study was to determine the correlation of exclusive breastfeeding towards decreasing of infectious diseases in infants aged 6-12 months. This study was conducted from March to April 2018. This study was a correlative analytic observational study with a historical cohort design. The subjects of this study were children aged 6-12 months in the working area of ​​Puskesmas Mlati II. Exclusive breastfeeding was assessed using interview and incidence of infectious diseases seen from medical records with a sample size of 130 babies with sampling using purposive sampling. The results showed that the low incidence of infectious diseases (60%) is greater than the high incidence of infectious diseases (40%). Statistical analysis with Chi-Square test obtained p value=0,000, so the analysis result was p<0.05 which showed that there was the correlation of exclusive breastfeeding towards the incidence of infectious diseases in infants aged 6-12 months. RR value 2,00 (95% CI 1,450-2,759) on the incidence of infectious diseases. Children who received exclusive breastfeeding had a decreasing incidence of infectious diseases 2,00 times greater than non-exclusive breastfeeding. Multivariate analysis obtained p value=0,017 means there was a correlation between exclusive breastfeeding, nutrition status, maternal education background, and socio-economic status to the incidence of infectious diseases in infants aged 6-12 months.